2023
DOI: 10.1149/1945-7111/ad0420
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed TiO2 Negative Electrodes for Sodium-Ion and Lithium-Ion Batteries Using Vat Photopolymerization

Alexis Maurel,
Ana C. Martinez,
Sina Bakhtar Chavari
et al.

Abstract: Additive manufacturing represents a unique approach to develop three-dimensional shape-conformable batteries with enhanced surface area, ion diffusion, and power. For the first time, a composite photocurable resin loaded with solid particles of active materials and conductive additives was prepared and used as feedstock to print negative electrodes for sodium-ion and lithium-ion batteries by means of a vat photopolymerization 3D printer. In alignment with NASA’s Artemis mission goals to develop sustainable lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…For the cathode containing 33 wt% of polymers, they reported a specific discharge capacity of 90 mA h g −1 at C/20 (56% of the practical capacity). From the same group, Maurel et al 40 recently reported a green state TiO 2 -based VPP printed electrode exhibiting low specific capacity when cycled versus Na/Na + (<10 mA h g −1 ). However, upon sintering in argon, high specific capacities of 60 and 115 mA h g −1 versus Na/Na + and Li/Li + , respectively were achieved.…”
Section: Resultsmentioning
confidence: 99%
“…For the cathode containing 33 wt% of polymers, they reported a specific discharge capacity of 90 mA h g −1 at C/20 (56% of the practical capacity). From the same group, Maurel et al 40 recently reported a green state TiO 2 -based VPP printed electrode exhibiting low specific capacity when cycled versus Na/Na + (<10 mA h g −1 ). However, upon sintering in argon, high specific capacities of 60 and 115 mA h g −1 versus Na/Na + and Li/Li + , respectively were achieved.…”
Section: Resultsmentioning
confidence: 99%